Struktur dan Fungsi Bahasa Mantra dalam Masyarakat Jawa (Sutasoma : Jurnal Sastra Jawa, 2023)
Mantra is a distinctive choice of words, the meaning of which can only be known through in-depth cultural reading based on the culture in which the mantra lives. This study aims to describe the structure and function of the mantra language in Javanese society. The research method uses a qualitative descriptive approach. Sources of research data are Javanese mantras collected by purposive sampling. Data were analyzed by semantic analysis. The validity of the data used is semantic validity with semantic analysis techniques. The results of research on Javanese mantras are as follows: 1) the structure of the spell consists of a title, opening, suggestion, purpose, and conclusion of the spell; 2) the function of the mantra based on the user's purpose is generally divided into individual functions and social functions. The cultural aspects surrounding the spell have certain functions which are believed to have magical powers by the people. In Javanese culture, mantras have a special position in the religious system and public beliefs. The community also believes that each mantra recited has a different function according to the contents of the mantra recited by the speaker. Keywords: function; Javanese; mantra; structure